Inspiratory muscle training in healthy individuals: randomized controlled trial - Esteves, Fábio (2022)
Introduction – Inspiratory muscle training (IMT) emerges as an important intervention in people with COPD, but above all with a growing interest in the healthy population. However, there are not enough studies to prove if inspiratory muscle training is also reflected in the improvement of the aerobic capacity objectified in oxygen consumption (VO2). Therefore, more investigation is relevant to understand the real relationship between IMT and its results on healthy people. Thus, it was considered appropriate to carry out a research study on a healthy population that would allow assessing to what extent an inspiratory muscle training program induces changes in inspiratory muscle strength and aerobic capacity. Methods and analysis – The sample was based on healthy individuals (n=19) between 18 and 21 years old who perform the regular physical exercise (≥ 3 times a week or ≥ 4 hours per week). The aerobic capacity was estimated by the Ebbeling Test and inspiratory muscle strength was measured by the maximum inspiratory pressure (MIP) obtained by a specific dynamometer (MicroRPM®) at two different times (pre and post-workout). The above-mentioned sample was randomly divided into two groups (n=9 in the experimental group and n=10 in the control group). The experimental group (EG) was subjected to a high-intensity IMT (≥50% Pi, max) while the control group (CG) didn´t go through any intervention. The IMT was performed by PowerBreathe Classic® Level 1 and Level 2 which provides consistent and specific pressure for inspiratory muscle strength regardless of the individual's inspiratory flow. Conclusions – After the training, there was a 37% increase in EG PIM while the CG showed an improvement of 7%. In intergroup comparison, both groups increased significantly both MIP and VO2 (p<0.05). However, comparing both groups, the differences were significant for the PIM (p=0.000), but not for VO2. Further studies are required to assess in which conditions IMT produces changes in aerobic capacity.